Strategy for Foreign Students’ Professional and Language Competence Development - E. S. Ionkina; O. S. Kharlamov (Высшее образование в России)
The authors propose a model of pre-master foreign students’ training, based on the formation of professional and language competence of foreign pre-master students during their studies at pre-university courses, and also consider pedagogical technologies of its implementation. Entering the pre-university courses, pre-graduate students have some skills in self-directed scientific research, but they cannot write in a non-native language, read professional literature, create their own scientific text and formalize a statement and present it. The authors propose a specific learning strategy that helps pre-graduate students to acquire oral and written language skills, produce a full monological scientific statement in Russian, get the initial skills in academic writing.Pre-Master’s training of foreign students is characterized by an individual approach to future undergraduates. Developing the strategy aimed at the achievement of the professional and language competences by foreign pre-graduates, the authors implement various learning methods, such as a personality-oriented method, grammar-translation method, communicative method of teaching and a project method. The article sums up the initial monitoring results of the program implementation at pre-university courses of Volgograd State Technical University and formulates the proposals for its further development. Strategic planning of teaching Russian in this direction allows us to rely on the fact that a foreign scientist would be able to solve specific communicative tasks in a non-native language in an academic and professional environment.